Global Goal on Adaptation - Njuguna, Lucy Wanjiku (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This learning note provides an overview of the Global Goal on Adaptation (GGA), highlighting its establishment in 2015 as a collective commitment to enhance adaptive capacity, strengthen resilience, and reduce vulnerability to climate change in line with the temperature goal of the Paris Agreement. It outlines the current progress in operationalising and measuring the GGA, describing key milestones such as the Glasgow–Sharm el-Sheikh (GlaSS) work programme and the ongoing United Arab Emirates (UAE)-Belem work programme on indicators. The note reviews the status of work on defining targets and indicators, and the persistent gaps and unresolved questions that hinder comprehensive assessment. Key takeaways include: the GGA will be critical in assessing adaptation progress under the Global Stocktake (GST) and despite the slow but steady advancement, the recent agreement on global targets marks a critical step forward. With less than six months remaining in the UAE-Belem process, broadening engagement and integrating diverse perspectives are now essential to shaping robust, inclusive indicators that can effectively inform the GST and support transformative adaptation action.